(3eONd JMdjdjs - (3cGed GdSjO(B, (3ZQGHs ((3GdQjGV(B:s (3LGeYI Gdedc SYhO(B,s)
(3GdEOGQI hfXe GdeYdheGJ(B- (3GdMGLI Gdi GdeYdheGJ(B- (3YfUQ GdEOGQI aj fXe GdeYdheGJ GdEOGQjI(B- (3YfUQ GdeYdheGJ aj fXe GdeYdheGJ GdEOGQjI(B- (3JWhjQ fXe GdeYdheGJ(B- (3HMK GdEMJjGLGJ hGdOQGSGJ GdJegjOjI(B- (3eQMdI GdJMdjd(B- (3COhGJ GdJMdjd Gdebff(B- (3EYJHGQGJ GdJUeje(B- (3NQjWI gjcd GdfXGe(B- (3EYJHGQGJ GdJWHjb(B- (3NWI GdENJjGQ hEYJHGQGJ GdLhOI(B- (3JTZjd GdfXGe hEOGQJg hJbhjeg(B- (3CeKdI JWHjbjI dfXe GdeYdheGJ GdEOGQjI(B- (3fXe EOGQI bhGYO GdHjGfGJ(B- (3fXe OYe GJNGP GdbQGQGJ(B.s
Keywords: (3GdeYdheGJ GdEOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s